WHEN I EMBODIED THE TRACE OF THE TRUE BANDIT. ROTOS BANDIDOS IN THE CHILEAN LITERATURE - Rojas Sotoconil, Araucaria (Revista de Historia Social y de las Mentalidades, 2012)
The following article seeks to reconsider  the discourses articulated around the  “bandidaje” from the field of literature in  Chile. Some of the questions explored are:  How is a bandido perceived by an external  observer? Or, Is there any coincidence  between the bandido established by  historiography and the one created by  literary texts? In this sense, special attention  is paid to the links between different  figures, namely the peón-gañán, roto  chileno and bandido, exploring also the  symbolic rupture implied in the practice  of bandidaje. Considering misfortune as a  transversal background, this essay exposes  the motives urging the bandido to become a  bandit. People’s poetry, romances, cuecas,  tales and novels - laid out on an extended  temporal framework - guide the analysis,  organized in terms of their subjects rather than  the chronology, in order to emphasizes certain  commonly used layouts in the configuration of  the imagery of the bandido.
Keywords: Literature; misfortune; roto chileno; bandit